Government Strategies In The Implementation Of Local Regulation Number 6 Of 2015 Concerning Waste Management In Bungo District (Study at the Bungo District Environment Office) - Fitri Arianti Saputri (PT. Anagata Sembagi Education, 2024)
The research location was carried out at the Bungo Regency Environmental Service. This research lasted for one month, namely August 2019. The research aims to determine the implementation of regional regulations regarding waste management in Bungo Regency based on Regional Regulation Number 6 of 2015 and to determine the obstacles in implementing Regional Regulation Number 6 of 2015 concerning waste management in Bungo Regency. This research uses a qualitative method where this research uses descriptive data in the form of written or spoken words from people and observable behavior.The results of the research show that the Environmental Service Strategy in Implementing Regional Regulation Number 6 of 2015 concerning Waste Management in Bungo Regency, which is described as a program for developing waste management performance as program implementers, is a program that was born to answer waste problems and optimize cleaning services and improve environmental cleanliness. and settlements to public spaces in Bungo Regency. In the explanation of the strategy of the Environmental Service in implementing the regional regulation policy, the program for developing the performance of cleanliness management for communication developed by the Environmental Service of Bungo Regency has not been implemented optimally. The obstacle in achieving the implementation of this policy is the rapid rate of population growth in Bungo Regency so that Waste production also increases. Low public awareness is one of the problems faced in implementing this strategic policy related to cleanliness management and the community's obligations towards the environment, namely the lack of public awareness in practice of always throwing rubbish not in the places provided by the Environmental Service. Furthermore, the obstacle in the Environmental Service's strategy in implementing the regional regulation is the inadequate facilities and infrastructure for cleaning management and the next obstacle is the lack of budget owned by the Bungo Regency Environmental Service so that implementing strategic policies is not yet optimal.